Makna Leksikal dan Kultural dalam Upacara Seren Taun Ritual Daur Hidup Manusia pada Masyarakat Sunda - Nissa Aurellia Putri; Nurhayati Nurhayati (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study aims to reveal the lexical and cultural meanings in the Seren Taun ceremony, one of the human life cycle rituals performed by the Sundanese people. This ceremony plays an important role in maintaining the social and spiritual balance of the community and preserving Sundanese cultural heritage. Using a linguistic anthropology approach, this study analyzes various terms and symbols used in the Seren Taun ceremony and examines how these meanings reflect the values and worldview of the Sundanese people. Data was collected through participatory observation and analysis of written documents related to the ceremony. The results of the study show that the lexical meaning in Seren Taun is not limited to the literal meaning of the words used, but also includes deep cultural connotations. Symbols such as rice, water, and fire in this ceremony contain meanings related to fertility, life, and purification. In addition, this study found that the Seren Taun ceremony serves as a medium to strengthen the collective identity of the Sundanese people and convey noble values such as mutual cooperation, togetherness, and respect for ancestors. Through this ceremony, the Sundanese people also pass on traditional knowledge and wisdom to the younger generation, ensuring the continuity of their culture amid changing times. This research contributes to a more comprehensive understanding of the relationship between language, culture, and rituals in Sundanese society. These findings also emphasize the importance of preserving local languages and cultures as part of national identity and world cultural heritage. Thus, this study provides valuable insights for researchers, cultural practitioners, and policymakers in their efforts to preserve and promote Indonesia's cultural heritage.